Effectiveness of Starfruit Leaf Tea in Reducing Blood Pressure in Pregnant Women with Hypertension - Septy Ariani; Nuraliyah Sugianti; Fila Fildilla (Indonesian Journal of Global Health Research, 2024)
Hypertension is a cause of maternal morbidity and mortality. Hypertension in pregnancy can cause complications such as thrombocytopenia, myocardial infarction, pulmonary edema, maternal death. The impact on the fetus is death and low birth weight (LBW). The impact of hypertension that can be dangerous and life-threatening, so it is necessary to do early treatment by providing pharmacological and non-pharmacological treatment. Starfruit leaves have several compounds such as potassium citrate which functions as a diuretic so that it can help to lower blood pressure, also has the potential as an antioxidant to lower blood pressure. The purpose of this study was to determine the effectiveness of giving starfruit leaf tea on reducing blood pressure in pregnant women with hypertension. The research method is Quasi Experiment pre-test and post-test with control group design, the study was conducted in Pasar Kemis District, Tangerang Regency, a sample of 30 respondents, namely 15 pregnant women as the intervention group and 15 pregnant women as the control group. Researchers conducted pre-tests and post-tests on respondents by measuring blood pressure. Researchers gave starfruit leaf tea to the intervention group for 7 days as much as 200 cc, data analysis using SPSS by conducting univariate and bivariate analysis using the Mann Whitney test. The results of the Mann-Whitney test of starfruit leaf tea intervention obtained a p-value of 0.001 for systolic pressure and diastolic pressure of 0.002 (<a = 0.05). This means that there is effectiveness between blood pressure before and after starfruit leaf tea is given to pregnant women with hypertension.